Modeling of InGaAs/InGaP/GaAs/AlInP/Ge-Based Five Junction Solar Module with Wafer Bonding for Efficiency Improvement - Hamidi, Muhammad Najwan; Shehram, Muhammad; A. Wahab, Aeizaal Azman; Mat Desa, Mohd Khairunaz (International Journal of Integrated Engineering, 2024)
Currently, a lot of works are done on solar PV modules to improve their efficiency. The world’s interest is developing towards the usage of solar energy, which is a clean and environmental friendly source of energy. The efficiency of a solar multijunction PV module is improved from the increasing number of junctions, but it also depends upon the quality of materials, their properties, and band gap energies. In this work, a five junctions solar module is designed where each junction contains its unique band gap energy. The high band gap energy materials encompass less lattice mismatched value while the low band gap materials have higher values. These mismatched materials are directly and electrically connected using wafer bonding. The AlInP relates to the window layer which improves the efficiency. Multijunction solar cells’ electrical components are determined by short-circuit current (Jsc), open-circuit voltage (Voc), peak power, and fill factors. The solar module with five junctions, utilizing InGaP/InGaAs/GaAs/AlInP/Ge, achieves enhanced efficiency of up to 46.7% when the materials have a standard band gap length of 1.5 Angstroms. Germanium is used as a substrate in the module in the bottom junction for the efficiency improvement of the multijunction PV modules. The simulation is done and the results are obtained through MATLAB/Simulink simulation.